Analyzing Posyandu Cadres' Motivation in Combating Stunting through the Lens of Maslow's Hierarchy of Needs - Naibili, Maria Julieta Esperanca; Rua, Yusfina Modesta; Seuk Asa, Sefrina Maria (Jurnal Pendidikan Keperawatan Indonesia, 2023)
Stunting, a common child malnutrition form, hampers growth due to poor nutrition, infections, and limited psychosocial stimulation. Primarily affecting those under five, especially in the first 1,000 days, it becomes nearly irreversible later. Linked to impaired brain development, childhood morbidity, and mortality, it heightens the risk of chronic diseases in adulthood, impacting cognitive function and productivity. This research aims to analyze factors related to the motivation of Posyandu cadres in tackling stunting in the Belu Regency, RI-RDTL border. The method used in this research is mixed methods. The mixed method research strategy applied is the Concurrent Embedded method. The quantitative method used is a descriptive approach while the qualitative method uses a case study. The study was conducted at Haliwen Health Center and South Atambua Health Center, with a quantitative research sample of 150 people and 10 qualitative research informants. The research findings indicate that the dominant cadre motivation factors include Social Needs at 99.3%. Based on Maslow's Basic Human Needs motivation factors, when viewed from the results of quantitative and qualitative data analysis, the motivation of cadres in handling stunting is social needs. Meanwhile, in qualitative research, a main theme was found, namely Humanitarian Harmony, which was divided into 3 categories, namely Volunteering, Dedication, and Caring. Volunteering, Dedication, and Caring are included in social needs. Humans in general need to interact and contribute to society. Dedication, caring, and volunteering are ways to fulfill this social need by providing support or assistance to others without expecting immediate reward.